A RETROSPECTIVE STUDY ON THE INCIDENCE OF MANDIBULAR CARCINOMA IN A UNIVERSITY SETTING - SS, Shivanni; Selvarasu, Kathiravan; R N, Balakrishna (International Journal of Psychosocial Rehabilitation, 2019)
Oral Squamous cell carcinoma is the most common oral cancer. The risk factors of carcinoma include tobacco chewing, smoking, alcohol use, viral infection, immunosuppression, chronic irritation. The aim of this study is to find the incidence of mandibular carcinoma in saveetha dental college.. The study was conducted using the records of patients who visited the Saveetha institute of oral oncology between June 2019-April 2020. The results were tabulated and statistically analysed using SPSS software. Descriptive statistics and chi-square tests were done. Mandibular carcinoma was present among 43.33% of the total study population. Patients with upper arch affected were 26.67% and both arch affected were 30%. Male predominance (92.31%) was seen compared to female (7.69%). The most common age affected by mandibular carcinoma was 40-49 years (46.15%). From this retrospective analysis we conclude that mandibular carcinoma prevalence was higher than maxillary carcinoma and carcinoma affecting both the jaws. There was male predilection with most cases occurring within the 4th decade of life. The most commonly affected site among patients with mandibular carcinoma was buccal mucosa (53.85%). Statistically no significant association was noted between patient age group and gender, age and site of carcinoma in mandible, gender and site of carcinoma in mandible (p value >0.05).